CULTURAL, SPIRITUAL COPING AND INNER CHILD REFLECTION: A MODEL FOR CROSS-GENERATIONAL MENTAL HEALTH PROMOTION IN ADOLESCENTS - Yuni Kurniawaty; Ni Luh Agustini Purnama; Irine Yunila Prastyawati; Baswara Yua Kristama; Dulce Giovania de Jesus; Fransisca Stefania Melinda Neolaka (The Indonesian Journal of Public Health, 2025)
Introduction: Adolescence is a developmental phase that is vulnerable to stress. A stress study of 1,344 participants aged 14-18 years old experienced moderate (22.8%), severe (43.0%), and very severe (16.8%) stress. Health promotion not only focuses on individuals but also considers local wisdom culture, spirituality, and intergenerational relationships. Aims: Develop a mental health promotion model based on local wisdom values, spiritual adaptation, and parental emotional literacy. Method: This study is a qualitative study with a population of adolescents in Bali, Yogyakarta, and Madura. The sample used purposive sampling of 20 informants, namely adolescents, teachers, and parents, through a phenomenological approach with in-depth interviews conducted from June to August 2025. The data analysis process included reduction, categorization, synthesis, and formulation of working hypotheses. Results: Five themes were identified: 1) Stress responses manifested through self-isolation, compensatory behavior, obsessive use of technology; 2) Cultural factors play a role in regulating emotional expression and as a source of social resilience; 3) Spirituality as a source of inner peace and meaning of life through prayer, rituals, and interfaith beliefs; 4) Parenting styles are influenced by children's inner experiences and past emotional states that impact adolescents' psychological well-being; and 5) Coping strategies: problem-focused coping, emotional coping, and avoidance coping, with varying effectiveness depending on social and spiritual support. Conclusion: An intergenerational mental health promotion model based on the development of local wisdom, spiritual coping, and emotion-based parenting is recommended as a holistic approach to improving adolescent mental health in Indonesia, synergistically involving families, schools, and communities.